THE IMPACT OF WORKING FROM HOME ON EMPLOYEE PRODUCTIVITY DURING 21ST CENTURY - Vasudevan, Asokan; Sivakumar, Meerankumar; Balakrishnan, Rajani (PEOPLE: International Journal of Social Sciences, 2021)
Companies are now being forced to shift operations out of the workplace and into their employees’ homes while doubts are still being cast if productivity would remain. When working from home, the factors influencing productivity have been put under the spotlight to see if they are significant as times call for work from home arrangements to be the subsequent new norm. The research was conducted to investigate the impact of working from home on employee productivity in the 21st century. The study has thoroughly examined academic papers and theories relevant to the area and settled on using Self-Determination Theory for this research. Self-Determination Theory speaks of the factors that affect an individual’s motivation and breaks what drives them into three basic human needs that need to be satisfied to feel motivated. This research’s primary data collection method was to use a well-structured questionnaire, and Statistical Package for the Social Sciences (SPSS) 26 was employed. The questionnaire was distributed to several different service industry organizations in Malaysia. The results determined that Autonomy had the highest Correlation and strongest determinant of employee productivity and proved to influence employee productivity alongside competence significantly.